Inovasi Reaktor Pirolisis Produksi Biochar Berbahan Baku Organic Waste Slurry Dari Sampah Perkotaan Terpilah Dengan Kontrol Tekanan - Tris Sugiarto; Sartohadi, Junun; Pulungan, Nur Ainun Harlin Jennie; Ngadisih, Ngadisih; Praharto, YB; Hidayati, Nurul (Sehati Abdimas, 2024)
The application of this technology aims to develop a pyrolysis reactor for Organic Waste Slurry, designed to convert urban organic waste into high-quality biochar, with a self-sufficient pressure control system for energy efficiency. The methodology employed in this study includes performance testing of the pyrolysis reactor equipped with automatic temperature control and a system to utilize pyrolysis gas as an internal fuel source. Organic waste was processed at pyrolysis temperatures ranging from 400–500°C to produce biochar with a high fixed carbon content. Testing was conducted on several soil samples with added biochar to assess its impact on water retention and nutrient availability. The results of the study indicate that the biochar produced from the Organic Waste Slurry reactor has a fixed carbon content of around 65–70%, along with optimal physical and chemical stability for use as a soil amendment. This biochar increased the cation exchange capacity (CEC) of the soil by up to 30% and improved soil water content by 15% compared to controls without biochar. Quantitatively, the reactor successfully reduced the volume of organic waste by 50% and generated biochar that enhanced soil fertility, positively impacting urban agricultural productivity. The mechanisms and processes in the Organic Waste Slurry pyrolysis reactor were found to be effective as a solution for urban organic waste management, reducing carbon emissions, and improving soil quality sustainably. This technology shows a positive trend in energy efficiency and applications for environmental agriculture and food security.